MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA MELALUI MODEL PEMBELAJARAN BIOLOGI REMAP STAD - Farqiyatur Ramadhan; Susriyati Mahanal; Siti Zubaidah (Pascasarjana Universitas Negeri Malang, 2017)
The aims of this study are to explore the effect of Reading-Concept Map- Student Team Achievement Division (Remap-STAD) towards cognitive learning outcomes on highschool students. This research is done in senior high school 1 Batu City, with participants as many as 70 students. This research used Nonequivalent Pretest-Posttest Control Group Design. The data cognitive learning outcomes obtained from essay tests amounted to 10 questions that refer to the revised Bloom's taxonomy. The test results were then analyzed with Anacova. The results of this experiment showed that Remap-STAD can enhance cognitive learning outcomes. Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran Reading-Concept Map-Student Team Achievement Division (Remap-STAD) terhadap hasil belajar kognitif siswa. Penelitian ini dilakukan di SMAN 1 Batu, dengan jumlah partisipan sebanyak 70 siswa. Rancangan penelitian yang digunakan adalah nonequivalent pretest-posttest control group design. Data hasil belajar kognitif diperoleh dari pemberian tes esai berjumlah 10 soal yang mengacu pada taksonomi Bloom yang sudah direvisi. Hasil tes selanjutnya dianalisis dengan teknik Anacova. Hasil penelitian menunjukkan bahwa Remap-STAD berpengaruh terhadap hasil belajar kognitif siswa.